Community-based Language Development of Northern Catanduanes, Philippines - Renelyn Bautista (Diversitas Journal)
This study determined the language status of Northern Catanduanes spoken in Caramoran, Province of Catanduanes, and a language spoken by the local folks but not widely used outside of their community. Conducted at the height of the pandemic, the Functions, Acquisitions, Motivations, Environment, and Differentiation (FAMED) conditions identified the common factors that determined the level of language use, while the Expanded Graded Intergenerational Disruption Scale (EGIDS) measured the level of language use and vitality. Ten participants who are native speakers were selected through purposive sampling based on the Sustainable Use Model (SUM) that provided the framework for evaluating the sustainability of Northern Catanduanes. The data were collected through online focus group discussions (FGD) and survey questionnaire. The findings suggest that the EGIDS level for Northern Catanduanes is Level 5 Developing, which means “the language is being used by some though this is not yet widespread or sustainable language is in vigorous use with literature in a standardized form.” It does not enjoy the same vigorous use and prestige as the other languages of the Bicol Region, because not much is written in Caramoranon; though the locals see its importance as they widely use the language. But it is not the dominant language in trade, government, and education. A coordination with the local education sector, Bicol University, and the Local Government Unit (LGU) for the creation of a working orthography of the Caramoran language is highly recommended by the key informants to reinforce the conditions of sustainable language use and the preservation of the local Caramoran language including comparative studies to gain insights about language vitality that may lead to crafting orthographies and strengthening the MTB-MLE program.